2006
DOI: 10.1111/j.1532-5415.2006.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and the Risk of Warfarin‐Associated Hemorrhage: The Anticoagulation and Risk Factors In Atrial Fibrillation Study

Abstract: OBJECTIVES-To assess whether older age is independently associated with hemorrhage risk in patients with atrial fibrillation, whether or not they are taking warfarin therapy. DESIGN-Cohort study.SETTING-Integrated healthcare delivery system. PARTICIPANTS-Thirteen thousand five hundred fifty-nine adults with nonvalvular atrial fibrillation.MEASUREMENTS-Patient data were collected from automated clinical and administrative databases using previously validated search algorithms. Medical charts were reviewed from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
414
6
23

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(452 citation statements)
references
References 36 publications
(63 reference statements)
9
414
6
23
Order By: Relevance
“…As previously reported, the rate of thromboembolism occurring without warfarin therapy was 2.5 per 100 person-years in the overall ATRIA cohort 10 and even higher in other cohorts 2,[20][21][22] ; these rates are reduced by more than 50% by warfarin therapy. 10,23 This benefit exceeds the additional risk of warfarin-associated intracranial hemorrhage (0.47 per 100 person-years with warfarin therapy compared with 0.29 per 100 person-years without warfarin therapy), 10,24 and the balance of risk to benefit seems to favor the use of warfarin for the typical patient with atrial fibrillation. 2 Nevertheless, there are likely to be subgroups of patients with atrial fibrillation for whom this balance is less favorable, making further work to identify these subgroups critical to optimizing the use of warfarin at the individual and population levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, the rate of thromboembolism occurring without warfarin therapy was 2.5 per 100 person-years in the overall ATRIA cohort 10 and even higher in other cohorts 2,[20][21][22] ; these rates are reduced by more than 50% by warfarin therapy. 10,23 This benefit exceeds the additional risk of warfarin-associated intracranial hemorrhage (0.47 per 100 person-years with warfarin therapy compared with 0.29 per 100 person-years without warfarin therapy), 10,24 and the balance of risk to benefit seems to favor the use of warfarin for the typical patient with atrial fibrillation. 2 Nevertheless, there are likely to be subgroups of patients with atrial fibrillation for whom this balance is less favorable, making further work to identify these subgroups critical to optimizing the use of warfarin at the individual and population levels.…”
Section: Discussionmentioning
confidence: 99%
“…Older age, elevated INR level, and history of ischemic stroke have all been identified as risk factors for intracranial hemorrhage, but because older age and prior stroke are also risk factors for ischemic stroke, additional investigation into unique risk factors for intracranial hemorrhage is clearly needed. 2,15,24 Modifiable measures, such as maintaining anticoagulation intensity within the therapeutic range of INR 2.0 to 3.0, can reduce but will not entirely remove the risk of bleeding associated with warfarin. 15,25 A study of Medicare patients with atrial fibrillation showed that a high fall risk was associated with an increased risk of intracranial hemorrhage, 16 although the high rate of ischemic stroke (13.7 per 100 person-years) among this subset of patients with a high fall risk made warfarin the preferred option for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…[383][384][385]. Czynniki ryzyka udaru mózgu i czynniki ryzyka krwawienia są częściowo wspólne (por.…”
Section: Kliniczne Skale Ryzyka Krwawieniaunclassified
“…385 Myocardial Infarction 48) trial, 321 edoxaban 60 mg once daily and edoxaban 30 mg once daily (with dose reductions in certain patients, Table 13), were compared with adjusted-dose warfarin. 405 Edoxaban 60 mg once daily was non-inferior to warfarin ( Table 13).…”
Section: Edoxabanmentioning
confidence: 99%